Running with Butkus: Animals and Animality in Rocky - Price, Jason (Humanimalia, 2014)
This essay examines the relationships between humans and animals in the first and last of the films in the Rocky series starring Sylvester Stallone. Analyzing the film’s engagement with capitalism, meat, and animals, the essay engages in discussion with Carol J. Adams work on women and meat as well as Haraway’s recent work on companion species. The essay looks at the ways in which Rocky and Adrian regard animals differently than the other characters in the film as they refuse to injure them or regard them merely as food for consumption; instead, Rocky keeps them as pets and Adrian works at a pet store. Lastly, I look at the scenes of Rocky training with dead animals, comparing these with the scenes where he trains with live dogs. I argue that the scenes of Rocky hitting the sides of beef in the meat locker serve to question the slaughter of animals while maintaining a humanist subject, whereas his training with Butkus performs more of a “posthumanist posthumanism,” to use Cary Wolfe’s term, as his subjectivity is constructed through his relating with his dogs.